An in situ high-temperature X-Ray diffraction study of phase transformations in maraging 300 steel - Reis, Adriano Goncąlves Dos [UNESP]; Reis, Danieli Aparecida Pereira; Abdalla, Antônio Jorge; Couto, Antônio Augusto; Otubo, Jorge (Trans Tech Publications, 2016)
An in situ high-temperature X-ray diffraction (HTXRD) study in maraging 300 steel was carried out to study the martensite to austenite transformation and effect of time of exposure in the austenite reversion below austenite start temperature. Solution annealed materials were subjected to controlled heating-holding cycles. The first sample was heated at a rate of 10°C/min from room temperature to 800°C, showing that the microstructure is completely martensitic (α110) until 600°C. From 650°C until 800°C, the microstructure is gradually changing from martensitic to austenitic, showed by the increasing peaks of λ111 and reducing peaks of α110. At 800°C the microstructure is completely austenitic (λ111). Another sample was heated at 10°C/min from room temperature to 600°C and held for 4 hours. At 600°C, at 0 h time of exposure, only a martensitic peak was observed. An austenite peak can be observed after some time of exposure at this temperature. The volume fraction of austenite increased with increasing time of exposure at 600°C, reaching 50/50 volume fraction after 4 hours of exposure. XRD diffraction patterns for the same sample that was held for 4 hours at 600°C and then cooled down in air to room temperature showed the same intensity of austenite and martensitic peaks found in situ at 600°C for 4 hours (retained austenite), with the volume fraction of 50/50 of austenite and martensite phases. The HTXRD technique can be used to identify and quantify martensite to austenite transformation and austenite retention.
Keywords: High-temperature X-ray diffraction; Maraging 300 steel; Phase transformation; Reverted austenite